ENTREPRENEURIAL PASSION, FAMILY BACKGROUND AND PERCEIVED UNIVERSITY SUPPORT ON CHINESE STUDENTS’ INTENTION AS ENTREPRENEUR - Xie Haozhe; Genoveva Genoveva (Faculty of Business, President University, 2023)
This study aims to investigate the reasons for the low entrepreneurial intention of college students in China. Currently, with China's low employment rate, entrepreneurship is one of the effective ways to increase employment. Although the government has introduced various entrepreneurship programs and initiatives, the effect is still not enough. The purpose of this research is to identify the factors affecting Chinese college students' entrepreneurial intention by studying the effects of entrepreneurial passion, family background, and perceived university support on entrepreneurial intention, and to propose effective suggestions to encourage more college students to start businesses. In this study, 131 valid data were finally collected through a survey of university students in different regions of China. And through the use of multiple regression and other questionnaire survey methods to analyze the questionnaire data. The research design will use a quantitative approach and use appropriate statistical methods to collect and analyze data. The results show that entrepreneurial interest, family background, and perceived university support have a significant effect on entrepreneurial intention. This study also found that all independent variables can affect entrepreneurial intention simultaneously. The implications of this study extend to various stakeholders, including universities, government, society, and families. The findings from this study will inform and support the development of targeted initiatives. To enhance Chinese university students' entrepreneurial intentions.